DEVELOPMENT OF FLASHCARD MEDIA BASED ON BLENDED LEARNING FOR PRIMARY SCHOOL TEACHER EDUCATION (PGSD) STUDENTS AT KHAIRUN TERNATE UNIVERSITY - Iwan Abdy; Lis Susilawati (Journey: Journal of English Language and Pedagogy, 2023)
Education is an aspect of life that is closely related to human life, and education is one of the pillars that plays an important role in creating quality people. This study is based on a lack of student understanding of the use of interesting media in the learning process. The purpose of this study is to develop and test the feasibility and effectiveness of a 'flashcard-based blended learning' media. The type of research is research and development using the ADDIE model. Research methods are analysis, design, development, implementation and evaluation. The subjects were 30 PGSD fifth semester students. Observations, tests, interviews, questionnaires, and documents are used to collect records. Data analysis techniques using product data analysis, initial data analysis, hypothesis testing, and n-gain testing. The results showed that the media "Flashcard based on blended learning" was very feasible to use with an average percentage of material expert judgment of 86.63% and 90.21% of media experts. he average score on the test went up by 72%, which is evidence that the test was measuring something important. The N-Gain calculation shows that the data is likely to be significant, which means that the average score between the pretest and posttest was different significantly. Research shows that flashcard-based learning media is a good way to learn at Khairun University. However, more research is needed to make sure the media is developed specifically for students there and that it is used in the best way possible.